PENGARUH PROGRAM PENINGKATAN PERAN EDUKATOR PERAWAT DALAM PELAKSANAAN DISCHARGE PLANNING TERHADAP KEPATUHAN UNTUK KONTROL KELUARGA RAWAT INAP DI RUMAH SAKIT JIWA DR. SOEHARTO HEERDJAN JAKARTA - Frida Anindit Yulianti (2023)
Discharge planning is a health service process that involves patients and families in preparing for discharge for continuity of care. Discharge planning or discharge planning is a systematic planning process that can be carried out in an inpatient room with one of the diseases. It is important for a nurse to carry out discharge planning optimally so that the patient has good readiness to go home. This study used a quasy experimental design. This writing aims to provide knowledge to nurses for patients or families to carry out discharge planning for compliance control for inpatients at RSJH Dr. Suharto Heerdjan Jakarta. From the results of the educational action, it was found that the knowledge of nurses increased from previously there were 3 nurses who had a low level of knowledge, 1 person with sufficient knowledge and 9 people with good knowledge, so there were no nurses who had less knowledge and only 2 nurses who are knowledgeable enough, while the other 11 people have good knowledge. From the results of carrying out the implementation of discard planning on patients, the results obtained are related to the level of patient compliance with control, namely the majority of respondents are at the level of adherence to frequency 10 with a percentage of 62.5% of the total 16 (100%) Respondents. It is hoped that hospital management will pay more attention restore the performance of nurses in the room so that the implementation of treatment and discard planning can be carried out and applied optimally in order to increase the knowledge of nurses and patients